Exploring the influence of funding sources on business incubation in the Western Cape - Milne, James (Graduate School of Business (GSB), 2021)
The topic of business incubation has been the subject of considerable academic research, and a focal point in entrepreneurship support ecosystems. Business incubators provide entrepreneurs and start-up businesses with a shared space (either physical or virtual). The incubator offers a systematic shared support structure that enhances businesses' chances of succeeding and growing into entities that eventually graduate to a location beyond the ‘safety net' of the incubator. Academic research in the field of incubation has predominantly focused on (i) understanding business incubation models that are most effective within particular operating environments; and (ii) understanding support services that are most useful to incubatees of the incubator. This research instead explores the influence that funding sources have on business incubators, with a focus on understanding how incubators in turn assist their incubatees in accessing finance. Research focusing on funder influence on incubators, and support provided to incubatees to assist with access to finance, is at a nascent stage within the South African business incubation landscape. The research was undertaken utilising a multiple case study approach, with individual business incubators constituting a case. Incubators were classified into three case typologies, depending on their predominant funding source: mixed; private; or public funded. From the population of business incubators in South Africa, a sample of 8 incubators within the Western Cape Province were selected. Semi-structured interviews with participants were undertaken over a three month period and involved undertaking interviews with 8 incubator managers, and 10 current or former incubatees. Qualitative data from participant interviews were analysed using a combination of NVivo12 and MS Excel, in order to determine responses relevant to the research question and subquestions. The information collected was categorised into themes of relevance using initial and pattern coding methodologies. The research suggests that funders influence the work of incubators through driving their own objectives, utilising the incubator as a tool. Public sector funders set objectives for incubators that were linked to achieving socioeconomic goals (poverty alleviation and economic redress). Public sector funders were found to be strongly focused on achieving their own performance indicator goals, even if these did not align to the work of the incubators. Private sector funders set objectives for incubators that were linked to achieving the goals of their organisation or fund mandate. Private sector funders were found to lack long-term commitment to funding incubators. Communication between public and private sector funders was found to be, in general, poorly co-ordinated. Lack of co-ordination between funders negatively affected the impact of incubators. The cross-case multiple case study methodology revealed that in the Western Cape, similarities exist in the channels of support provided by incubators to assist their incubatees in accessing funding, regardless of the funding structure of the business incubator. However, heterogeneous priorities exist in funding support services provided to incubatees. Bias was identified in the process of sourcing of funding for incubatees. Incubators pursued a blend of proactive and reactive approaches to accessing funding for their incubatees, depending on their relationship with funder(s). The researcher recommends a strengthening of efforts to co-ordinate objectives across the two broad spheres of incubator funding sources (public and private) in order to build effective and sustainable business incubators in South Africa. Financiers of incubators should review stakeholders and other financiers involved in the incubator to clarify policy, commitments and performance metrics. Emphasis must be placed on ensuring alignment (i) between incubator financiers; (ii) between the objectives of the financier(s) and the incubator. The current study is well suited to being expanded in future, both in terms of: (i) widening the interview participant base to include incubator financiers; (ii) a geographic expansion to focus on South Africa as a whole.